Responding to the world food crisis-- Getting on the Right Track: IFPRI 2007-2008 Annual Report Essay - von Braun, Joachim (International Food Policy Research Institute, 2008)
Part of the difficulty in responding to the food crisis is the lack of credible and up-todate data on the impacts of food prices on poor people and on the effects of policy responses. Such information would allow international and national decision makers to use feedback to adjust their responses and achieve maximum effectiveness. Much more investment and sound coordination is needed in this area. So far, national and international responses to the food crisis are mixed in terms of their likely effectiveness. Important steps have been taken with regard to emergency humanitarian assistance and, in some countries, social protection, but more is needed. Some countries and institutions are launching substantial investments in agricultural production, but, again, meeting global demand for food will require even greater investments. And, in the areas of trade and biofuel policies, many of the actions taken are counterproductive and actually put more upward pressure on food prices. It is promising that the issue of global food security is now on the agenda of the Group of Eight countries, but disappointing that at their July 2008 meeting they did not do more to promote social protection, revise biofuel policies, make specific commitments for funds to overcome the food crisis, or delineate the actors and mechanisms that would play roles in strengthening the global governance architecture for food and agriculture. It is crucial that the funds already committed by the G8 countries be released in a timely manner. What will it take to get food crisis responses on the right track? First of all, leadership is needed to coordinate implementation of appropriate responses. This effort could be led by the UN, as a follow up to the Group of Eight + Five countries' activities, and by major groups of developing-country players. At the moment, high and unstable food prices look like they are here to stay for some time-perhaps years. But because no one actually knows what the future holds, it is important that responses to this crisis help build the kind of food and agriculture system that can cope with a variety of possible outcomes, ranging from even higher food and energy prices to a possible short-term glut of low-priced food emerging from the current high-price environment and a world in which demand collapses due to recession. Millions of poor people would benefit from a system that would allow policymakers and others to respond calmly and rationally to eventualities like these instead of lurching from crisis to crisis. Building such a system will require collective action on an international scale. Given the strong links that tie so many countries to each other and to the world market, each country's actions inevitably have implications for others, so areas of common interest must be identified and trade-offs made. Moreover, these changes need to be made now, for the benefit of all people today and in the future.